Experimental and density functional study of Mn doped Bi₂Te₃ topological insulator - Ghasemi, A; Kepaptsoglou, D; Figueroa, A; Naydenov, G; Hasnip, P; Probert, M; Ramasse, Q; van der Laan, G; Hesjedal, T; Lazarov, V (American Institute of Physics, 2016)
We present a nanoscale structural and density functional study of the Mn doped 3D topological insulator Bi2Te3. X-ray absorption near edge structure show that Mn has valency of nominally 2+. Extended x-ray absorption fine structure spectroscopy in combination with electron energy loss spectroscopy (EELS) shows that Mn is a substitutional dopant of Bi and Te and also resides in the van der Waals gap between the quintuple layers of Bi2Te3. Combination of aberration-corrected scanningtransmission electron microscopy and EELS show that Mn substitution of Te occurs in film regions with increased Mn concentration. First-principles calculations show that the Mn dopants favor octahedral sites and are ferromagnetically coupled.